Understanding the regenerating capacity on photodegradation of methylene blue of titania supported mesoporous silica with the aid of gelatin-P123 as bitemplate - Ulfa, Maria; Hasanah, Ika Uswatun; Bahruji, Hasliza (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
Mesoporous silica (MS) was successfully synthesized via the sol-gel method using gelatin-P123 as a bi-template under hydrothermal reaction conditions at 100 ºC for 24 h, followed by calcination at 550 ºC for 5 h. The amount of TiO? in MS was adjusted to 1, 5, and 10% (w/w) and characterized using XRD, FTIR, SEM-EDX, N? adsorption-desorption, and UV-Vis. The crystallinity of the samples increased with higher TiO? content, as confirmed by XRD data. SEM analysis revealed that the morphology of MS and TiO?/MS was cylindrical, with a particle size distribution of 0.4–0.6 µm. The surface area of MS was 500.8 m²/g, which decreased to a range of 369.6–454.8 m²/g after TiO? modification, while the pore diameter increased from 28.22 to 34.61 Å. The adsorption efficiency for methylene blue photodegradation reached a maximum value of 95%, demonstrating excellent catalytic performance. Thermal regeneration proved to be a promising strategy to recover the photocatalytic efficiency of TiO?/MS for more than five cycles. Furthermore, thermal regeneration and the reuse of catalysts in wastewater treatment systems provide cost-effective solutions for pollutant removal.